2006
DOI: 10.1542/peds.2005-0775
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Stability, and Outcomes of Cry-Fuss and Sleep Problems in the First 2 Years of Life: Prospective Community-Based Study

Abstract: Most cry-fuss and sleep problems in the first 2 years of life are transient. Persistent, rather than transient, problems contribute to maternal depression, parenting stress, and subsequent child behavior problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
188
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(215 citation statements)
references
References 24 publications
7
188
2
3
Order By: Relevance
“…The effects faded by 6 months, which may reflect the natural improvement in infant crying and daytime sleep. 2,5 Unlike previous prevention trials aimed at improving infant nighttime sleep duration, 9,11,30,35 we found no such improvement. This is despite our program including similar information.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The effects faded by 6 months, which may reflect the natural improvement in infant crying and daytime sleep. 2,5 Unlike previous prevention trials aimed at improving infant nighttime sleep duration, 9,11,30,35 we found no such improvement. This is despite our program including similar information.…”
Section: Discussioncontrasting
confidence: 74%
“…[1][2][3] They are associated with maternal depression, premature weaning, and frequent formula changes. 4,5 Formula changes often occur when infant crying is misdiagnosed as gastroesophageal reflux or food allergy. 6 Infant crying is the most common proximal risk factor for abusive head trauma.…”
mentioning
confidence: 99%
“…Pediatrics 2013;131:e1857-e1864 1 and occurs in ∼20% of infants. 2 Colic is stressful for caregivers and is associated with elevated depression risk in the postpartum period in several cross-sectional and longitudinal studies. [3][4][5][6] Because maternal depression is a highly prevalent mental health disorder 7,8 and is associated with adverse child social-emotional and cognitive outcomes, 9 efforts to prevent or intervene early in the course of maternal depression are important to reduce depression-related morbidity in both mother and child.…”
Section: Resultsmentioning
confidence: 99%
“…Outros estudos corroboram esses achados 6,9,14,15,21 , mas não foi encontrado nenhum estudo brasileiro que avaliasse a associação entre o quadro depressivo materno e os comportamentos de sono infantil. A hipótese de que as mães deprimidas encontram mais dificuldades para regular o afeto, compreender e responder adequadamente as necessidades dos seus bebês e são mais inconsistentes e ineficazes no manejo com a criança deve ser considerada, uma vez que esses aspectos teriam um papel fundamental na regularização dos padrões do sono 6 .…”
Section: Discussionunclassified